The Anthropocene reviewed [compact disc, unabridged] : essays on a human-centered planet - Green, John, 1977- (Penguin Audio, 2021)
The Anthropocene is the current geological age, in which human activity has profoundly shaped the planet and its biodiversity. In this remarkable symphony of essays adapted and expanded from his groundbreaking podcast, John Green reviews different facets of the human-centered planet--from the QWERTY keyboard and Staphylococcus aureus to the Taco Bell breakfast menu--on a five-star scale. John Green's gift for storytelling shines throughout this artfully curated collection that includes both beloved essays and all-new pieces exclusive to the book.